Method of drawing elliptical points in the isometric form of a circle - Akhmedov Nurali Odilovich. (Academia One Publishing, 2023)
Creating ellipses dots from graphic method is offered in this article. In this case, the graphical method for constructing an ellipse is described in detail, and it is recommended to use it in modern architecture of buildings, since ellipsoids provide structural strength and have an excellent appearance
Keywords: ellipsoid; thin-walled shells; the axis of rotation of the cone